Effects of microwave, ultrasound, and various treatments on the reduction of antinutritional factors in elephant foot yam: A review. Issue 6 (3rd November 2022) - Srivastava, Shivangi; Pandey, Vinay K.; Singh, Poornima; Bhagya Raj, Gurajala Venkata Siva; Dash, Kshirod K.; Singh, Rahul
Abstract: Elephant foot yam (EFY) includes a high degree of nutritious fiber, carbohydrates, glucose, protein, and sugars. It also has plenty of calcium, sodium, potassium, and vitamin C, and is a promising source of starch. Due to the presence of oxalate and acridity, EFY has been extensively underused. Researchers have employed a variety of ways to decrease calcium oxalate, including boiling and NaCl treatment. A novel technique like ultrasound is a promising technique for the reduction of antinutritional factors effectively by keeping the natural phytoconstituents in it. The reduction of antinutritional factors by ultrasonication resulted from the high temperatures and pressures generated amid the collapse phase of cavitation bubbles. Microwave heating depends on the dielectric properties of the food. The dielectric constant is the ability to absorb the energy, and dielectric loss is the ability to reflect where it is dissipated as heat. Because of its heat‐labile nature and the formation of insoluble complexes, microwave treatment reduces the antinutrient component. This review focused on several studies on yam oxalate concentrations that were conducted using various treatments. This would help researchers and the food industry find more effective strategies to reduce the antinutritional factor using frequency‐controlled power ultrasound. Abstract : Dipole rotation and ionic conduction were the two phenomena used in the microwave heating of food products. Because antinutritional factors are heat‐labile, the heat created within the food by microwave and ultrasonication mechanisms leads to a reduction of antinutritional factors. Thermal degradation, structural denaturation, and the production of insoluble complexes are the primary causes of antinutritional factor depletion in elephant yam.